PENGARUH FASILITAS KERJA, LINGKUNGAN KERJA NON FISIK DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Pegawai Dinas Perindustrian dan Perdagangan Provinsi Jawa Tengah) - Anam, Khoirul; Rahardja, Edy (Diponegoro Journal of Management, 2017)
Human resources are the most important part to carry out the task and achieve the goal. From the results of employee performance data of the Industry and Trade of Central Java province occurred fluctuation. According to previous researchers factors of work facilities, non-physical work environment and job satisfaction affect employee performance. The purpose of this study to determine the effect of work facilities, non-physical work environment and job satisfaction on employee performanceData collection method used in this research is questionnaires dissemination by using purposive sampling method, the sample used in this research is employees of Industry and Trade Service of Central Java Province as much as 78 respondents who have working period more than four (4) years. This research uses data analysis methods such as validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, F test and t test.The results of this study indicate that work facilities, non-physical work environment and job satisfaction affect employee performance. Adjusted R Square value of 55.2%, which means that performance can be explained by the variable working facilities, non-physical work environment and job satisfaction. The remaining 44.8% can be explained by other variables.